Felicities in Chinese Web Novel Genres. - Yang, Renren (Chinese Literature & Thought Today, 2024)
This introduction considers genre fiction as a field of popular cultural production that breeds generic hybridity and diversity while seeking differentiation from mainstream genres in contemporary Chinese literature. It presents the "newness" of Chinese web novels as rooted in the digital mediascape they inhabit, where the production, circulation, and consumption of popular genres align with new media principles. Countering dismissive views on genre fiction, it demonstrates how web-based fiction genres engage with historical, social, and political realities, showcases the interplay between literary fiction and genre fiction, and advocates for a shift from text-focused to context-sensitive genre criticism where popular genres are repositioned within a broader technological, industrial, and social framework. Finally, the introduction envisions a sensuous form of unalienated playbour in the excessive and abundant customization of Chinese web novel genres.